Team reflections: how co-created knowledge objects enhance knowledge integration. Issue 4 (4th July 2021) - Teh, Yong Guang; Pang, Nicholas Tze Ping; Shoesmith, Wendy Diana; Loo, Jiann Lin; Teh, Swe Jyan
ABSTRACT: The general purpose of this study was to deepen our understanding of how co-created knowledge objects enhance knowledge integration in teams. The specific aim of this study was to develop a phenomenological model that can be used for studying the co-construction of knowledge objects. Our working assumption was that personal and group reflections are a rich source of perceptual and processual data that can be used to help build a model of how objects assist teams in integrating knowledge and coordinating complex, time-sensitive tasks. We examined the collective experience of how a newly formed debate team used co-created knowledge objects and achieved a higher level of knowledge integration to effectively deploy coordinated responses in a formal debate competition. In this paper, we present our emergent methodology of constructing a phenomenological model to describe the dynamic functions of co-created knowledge objects across personal and social realms.